Youth ministry: A system of support for responsible citizenry for South African youths - Garth Aziz (HTS Teologiese Studies/Theological Studies)
South Africa is both politically and demographically a young nation, presenting unique opportunities and challenges for youth engagement in civic life. With over 60% of the population under the age of 35 years, young people hold significant potential to shape the country’s future. However, lingering socio-economic inequalities from the apartheid era – such as extreme poverty, high unemployment, and limited access to quality education – continue to hinder youth participation in meaningful civic action. This article argues that youth ministry, when framed within the paradigm of public practical theology (PPT), can serve as a transformative agent for civic responsibility and social change.